White fragility why it's so hard for white people to talk about racism - DiAngelo, Robin (Boston Beacon Press, 2018)
Anger. Fear. Guilt. Denial. Silence. These are the ways in which ordinary white people react when it is pointed out to them that they have done or said something that has - unintentionally - caused racial offence or hurt. After, all, a racist is the worst thing a person can be, right? But these reactions only serve to silence people of colour, who cannot give honest feedback to 'liberal' white people lest they provoke a dangerous emotional reaction.
Includes bibliographical references.
Keywords: Racism